Artificial Intelligence in Education: Opportunities and Ethical Considerations - Bhawana Sangeet (AG Volumes, 2024)
The implementation and progression of Artificial Intelligence (AI) technologies within the realm of education have generated substantial discourse and prompted ethical deliberations. Although there is considerable discourse surrounding the potential benefits of AI in education, the ethical ramifications that stem from its conception and advancement have received comparatively less attention. The principle purpose of this paper is to investigate AI in field of education in order to identify its various opportunities/benefits and ethical implications. Additionally, an effort has been made to examine AI through the lens of NEP 2020.